The impact of futures price volatility to spot market: case of coffee in Indonesia - Wulandari, Anis Erma; Harianto, Harianto (Jurnal Organisasi dan Manajemen, 2019)
Indonesia is the world 4th largest coffee producer with export potential and higher national consumption concluded in 2017 while the coffee production was relatively stagnant. This was led the producer to not only the production risk but also the price risk which then emphasize the importance of futures markets existence as price risk management. This study is performed to examine the impact of futures price volatility to spot market using ARCH-GARCH toward primary data of coffee futures and spot prices of 1172 trading days starting from January 2014 to June 2018. Analysis result indicates that spot price volatility increase due to the volatility of futures prices and exchange rate volatility is also found influencing the volatility of local spot price. This is confirming that futures market plays dominant role in spot price discovery and exchange rate confirms Indonesia as coffee exporting country. Local futures prices are also found to be significantly influenced by volatility of offshore futures prices which indicates that emerging country futures exchange may actually influenced by develop futures market.